(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
Harmonisation of Ukrainian standards for agrochemical soil analysis with European Union requirements is a critical prerequisite for Ukraine’s successful European integration and modernisation of the agricultural sector. As of 2025, Ukrainian soil analysis practices are characterised by fragmentation, the absence of a comprehensive national integrated system, and reliance on mixed DSTU/GOST standards instead of codified national norms, which contrasts sharply with the new European Union Directive on soil monitoring and sustainability, which comes into force in December 2025. Purpose. Comprehensive analysis of technical, regulatory and institutional differences between Ukrainian and European standards for agrochemical soil analysis, identification of specific methodological gaps and development of a practical step-by-step harmonisation plan that takes into account the specifics of Ukrainian soil types, financial constraints and the requirements of the European regulatory environment. Methods. Comparative analysis of the Ukrainian regulatory framework and European Union regulatory requirements, systematic review of methodological differences in analytical protocols, assessment of the infrastructure needs of Ukrainian laboratories, and analysis of international accreditation experience. The expert assessment method was used to identify priority areas for harmonisation and calculate the financial costs of modernising laboratory infrastructure. Results. Critical methodological differences were identified in five key areas of soil analysis. Acidity measurement is characterised by the use of different electrolyte solutions and calibration protocols between Ukrainian laboratories and European standards, leading to systematic deviations in indicators and complicating the interpretation of nutrient availability. The determination of organic matter in Ukrainian practice is based on modified Soviet methods with limited standardisation, while European laboratories use loss on ignition or Walkley-Black methods, which creates incomparability of data on soil carbon stocks. Heavy metal analysis demonstrates the absence in Ukrainian standards of a comprehensive framework for new pollutants, including perfluoroalkyl and polyfluoroalkyl substances and modern pesticides, which are specifically required by the new Soil Monitoring Directive. Sampling protocols in Ukraine lack standardisation of grid density, depth procedures and composite sampling strategies necessary to ensure comparability of data between European Union member states. The quality assurance systems of Ukrainian laboratories need to be aligned with the accreditation requirements of the international standard 17025:2017 and regular proficiency testing programmes recognised at European level. It has been established that a typical regional laboratory requires an investment of €500,000–800,000 to upgrade its analytical equipment, including inductively coupled plasma systems with optical emission spectrometry costing €150,000–300,000, pH meters with standardised electrode systems costing €5,000–15,000, and equipment for analysing organic substances costing €20,000–50,000. National implementation requires a total investment of €50–80 million over three to five years. A five-stage implementation plan has been developed with a timeframe of 48–72 months, covering legislative reforms with the updating of standards and accreditation criteria during the first 12–18 months, infrastructure modernisation over 12–48 months, staff training through exchange programmes with European laboratories over 18–60 months, method validation through interlaboratory studies over 24–60 months, and full integration with European-level recognition. The need to establish a National Soil Monitoring Coordination Committee for inter-agency coordination, development of a national monitoring strategy and securing international funding through technical assistance programmes has been identified. Conclusions. Successful harmonisation of soil analysis standards will provide Ukrainian agriculture with improved access to the single market of the European Union by removing technical barriers to trade, increase confidence in Ukrainian products on international markets by demonstrating compliance with the gold standard of quality assurance, strengthen positions in carbon emission quota markets by providing reliable, verified data on organic carbon sequestration by soil, and promote the implementation of sustainable soil management practices based on accurate soil condition data. Practical value. The study provides a concrete action plan for government agencies, scientific institutions and agricultural laboratories with detailed cost estimates, implementation timelines and priority areas for modernisation, enabling effective investment planning and coordination of efforts at the national level to achieve full compliance with European Union requirements.